Rozwiąż reakcje zobojętniania
HNO3 + NH4OH
H2S + NH4OH
H3PO4 + NH4OH
H2SO4 + NH4OH
H2SO3 + NH4OH
H2CO3 + NH4OH

HNO3 + NA OH
H2S + NA OH
H3PO4 + NA OH
H2SO4 + NA OH
H2SO3 + NA OH
H2CO3 + NA OH


HNO3 + KOH
H2S + KOH
H3PO4 + KOH
H2SO4 + KOH
H2SO3 + KOH
H2CO3 + KOH


1

Odpowiedzi

2010-02-10T19:47:52+01:00
HNO3 + NH4OH = NH4NO3 + H2O
H2S + 2NH4OH = (NH4)2S +2 H2O
H3PO4 + 3NH4OH=3 (NH4)3PO4 +3 H2O
H2SO4 +2 NH4OH =( NH4)2SO4 +2 H2O
H2SO3 + 2NH4OH = (NH4)2SO3 + 2H2O
H2CO3 + 2NH4OH = (NH4)2CO3 + 2H2O

HNO3 + NA OH = NaNO3 + H2O
H2S +2 NA OH = Na2S + 2H2O
H3PO4 + 3NA OH = Na3PO4 + 3H2O
H2SO4 + 2NA OH = Na2SO4 + 2H2O
H2SO3 + 2NA OH= Na2SO3 + 2H2O
H2CO3 + 2NA OH = Na2CO3 + 2H2O

tu identycznie jak powyzej
HNO3 + KOH
H2S + KOH
H3PO4 + KOH
H2SO4 + KOH
H2SO3 + KOH
H2CO3 + KOH
1 1 1